Strategi Everyone Is A Teacher Here dalam Meningkatkan Keaktifan dan Kemandirian Belajar Peserta Didik pada Mata Pelajaran Pendidikan Agama Islam dan Budi Pekerti di Kelas VIII SMP Negeri 23 Kerinci - Pandika Pandika; Gusril Kenedi; Muhammad Zalnur (Pusat Riset dan Inovasi Nasional, 2024)
A learning strategy is a method chosen to convey lesson material. For this reason, strategy has a very influential position in the learning process. In this research, the author tested the Everyone Is A Teacher Here Strategy in Increasing Students' Learning Activeness and Independence in Islamic Religious Education and Character Subjects in Class VIII of SMP Negeri 23 Kerinci. The aim of this research is to determine the increase in learning activeness and learning independence of students in Islamic Religious Education and Character Education subjects in class VIII SMP Negeri 23 Kerinci after implementing the everyone is a teacher here strategy. The type of research carried out is quasi experiment. The research subjects were students in class VIII of SMP Negeri 23 Kerinci who were registered in semester 2 (even) of the 2022/2023 academic year, totaling 134 people. The research sample was chosen randomly consisting of an experimental class and a control class with a sample size of 34 people for each class. The research variables consist of one independent variable, namely; The Everyone Is A Teacher Here strategy and the two dependent variables, namely, Learning Activeness and Independence used are questionnaires. Hypothesis testing is carried out to determine the significant effect of the strategy implemented. The results of data analysis show that (1) There is a significant increase in students' learning activeness in the subjects of Islamic Religious Education and Character in class VIII SMP Negeri 23 Kerinci after implementing the Everyone Is A Teacher Here strategy. The results of hypothesis testing are statistically significant because the tcount value (5.683) > ttable value (1.669), so Ho is rejected and Ha is accepted; (2) There was a significant increase in students' learning independence in Islamic Religious Education and Character Education subjects in class VIII of SMP Negeri 23 Kerinci after implementing the Everyone Is A Teacher Here strategy. The results of hypothesis testing are statistically significant because the tcount value (5.148) > ttable value (1.669), so Ho is rejected and Ha is accepted.